Translation Techniques in Translating Social Terms into Indonesian used in the Novel to Kill a Mockingbird by Harper Lee - Zainuddin Hasibuan (Medan Resource Center, 2025)
This study examines the translation techniques used to render social terms from English into Indonesian in Harper Lee’s novel To Kill a Mockingbird, focusing on how culturally embedded expressions are transferred while preserving their semantic and sociocultural integrity. The research investigates two central questions: (1) which translation techniques—based on Molina and Albir’s (2002) framework—are applied in translating social terms, and (2) how these techniques affect the representation of social meanings in the target text. Using a qualitative descriptive approach, the study analyzes ten selected sentences containing socially significant terms from both the source and target texts. The findings reveal that 70% of the data employ couplet techniques, 20% apply single techniques, and 10% utilize triplet techniques. These strategies help maintain meaning equivalence, cultural nuance, and stylistic features of the original work. The study concludes that the translator’s sensitivity to sociocultural contexts is essential for ensuring cross-cultural comprehensibility, particularly when translating social concepts embedded in literary narratives.